2017
DOI: 10.5114/reum.2017.67605
|View full text |Cite
|
Sign up to set email alerts
|

The human body as an energetic hybrid? New perspectives for chronic disease treatment?

Abstract: Inflammatory response is accompanied by changes in cellular energy metabolism. Proinflammatory mediators like plasma C-reactive protein, IL-6, plasminogen activator inhibitor-1, TNF-α or monocyte chemoattractant protein-1 released in the site of inflammation activates immune cells and increase energy consumption. Increased demand for energy creates local hypoxia and lead in consequence to mitochondrial dysfunction. Metabolism of cells is switched to anaerobic glycolysis. Mitochondria continuously generate free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Neuroinflammation is a significant cause of degenerative diseases of the CNS. The activation of the immune system of the body will increase energy consumption ( Straub, 2012 ), and the increase in energy metabolism requirements of the body will lead to disorder in mitochondrial function, such as transformation of metabolism from aerobic oxidation to anaerobic glycolysis and increased release of free radicals, leading to oxidative stress ( Gajewski et al, 2017 ). From a pathological point of view, a class of protein-related neurodegenerative diseases, such as ALS, AD, and PD, is caused by misfolding and changes in the process of protein synthesis, as well as blockages in the degradation pathway of the endoplasmic reticulum, leading to abnormal accumulation of toxic proteins and ultimately neurodegeneration.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Neuroinflammation is a significant cause of degenerative diseases of the CNS. The activation of the immune system of the body will increase energy consumption ( Straub, 2012 ), and the increase in energy metabolism requirements of the body will lead to disorder in mitochondrial function, such as transformation of metabolism from aerobic oxidation to anaerobic glycolysis and increased release of free radicals, leading to oxidative stress ( Gajewski et al, 2017 ). From a pathological point of view, a class of protein-related neurodegenerative diseases, such as ALS, AD, and PD, is caused by misfolding and changes in the process of protein synthesis, as well as blockages in the degradation pathway of the endoplasmic reticulum, leading to abnormal accumulation of toxic proteins and ultimately neurodegeneration.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Indeed, indirect calorimetry was shown to overestimate EE when the RMR was not properly assessed (Fares et al, 2008). Therefore, RMR estimation is highly recommended to avoid bias, particularly as it was shown to be altered in many clinical conditions (Agiovlasitis et al, 2012, Alawad et al, 2013, Gajewski et al, 2017, Mahler et al, 2012, Montaurier et al, 2007, Nawata et al, 2004, Serra et al, 2015, Wens et al, 2014). Alternatively, METs can be used to estimate EE; Serra et al (Serra et al, 2017) found METs to be the strongest predictor of activity counts, despite explaining only 65% of the accelerometer activity counts.…”
Section: Calibration Protocol For Clinical Populationsmentioning
confidence: 99%
“…Under the pressure of hypoxia, several crucial metabolic cell steps undergo dramatic changes that can be divided into three stages [10].…”
Section: Hypoxia the Keystone Of Inflammationmentioning
confidence: 99%